Treatment Intensity: Considering Persons with Autism Spectrum Disorder and Intellectual Disability Who Have Complex Communication Needs. (September 2021) - Reichle, Joe; Ganz, J. B.; Pierson, Lauren; Rodriguez, Daira
Treatment intensity is an aspect of communication intervention that has received limited empirical attention. In this article, we discuss key parameters of treatment intensity related to individuals with complex communication needs who use augmentative and alternative communication. We advocate for an examination of treatment intensity along with learner and intervention characteristics that may moderate or mediate treatment intensity. In addition, we discuss the influence that contextual fit/treatment acceptability may have on intervention success. We also discuss the challenges created by a number of interacting variables that make determining optimal dosage for groups of individuals difficult. Finally, treatment intensity is briefly discussed in terms of its possible influence on maintenance and generalization.